Determining the relative importance of key drivers influencing source separation behaviour of waste producers - Namrata Mhaddolkar; Severin Fuchs; Lázaro V. Cremades (Discover Sustainability)
Abstract The European Union aims to recycle 60% of its total waste by 2030, for which waste collection infrastructure and the source-separation behaviour of waste producers are among the crucial prerequisites. Proper source separation increases the chances of waste getting recycled. For this, identifying the key drivers influencing the source separation behaviour is crucial. The present study identified 12 drivers for each non-demographic and demographic category from 43 scientific publications and calculated their relative importance based on the perceptions of three groups: (i) the expert group, (ii) the population group from Leoben (Austria), and (iii) population group from Barcelona (Spain). Using the pairwise comparison matrix of the Analytical Hierarchy Process, weights were calculated based on the relative importance of the drivers. From the non-demographic category, ‘Beliefs and values’, ‘Environmental concern’, and ‘Habits’ were rated as most important, while from the demographic category, ‘Level of education’ and ‘Location’ had the highest importance. The results were discussed in terms of biodegradable plastic waste.